KINERJA ANGKUTAN UMUM PENUMPANG PERKOTAAN DI KOTA KENDARI - Soeparyanto, Try Sugiyarto; Statiswaty; Arsyad, La Ode Muhammad Nurrakhmad; Masikki, Sultan Machmud Hasan (Jurnal Transportasi, 2023)
The improvement of community mobility is closely tied to the availability of adequate public transportation, one of which is city transportation. City transportation is one of the most effective modes for urban transportation. This needs to be complemented by an enhancement in the quality of service provided by city transportation fleets. This research aims to assess the operational performance of public transportation routes in Kendari City. The research methodology employs both dynamic (in-vehicle) surveys and static (road section) surveys. The parameters used to analyze operational performance and measure the route's requirements include frequency, load factor, time headway, travel time, passenger count, availability, and circulation time. A weighting system is applied using five criteria: Very Good (5), Good (4), Average (3), Poor (2), and Very Poor (1). The results of the research indicate that the city transportation route R.01/R.02 falls under the Good category, while the other six routes are categorized as Average. Parameters such as Frequency, Time Headway, and the Number of Operational Vehicles for all routes are in the Very Good criteria. However, the Load Factor parameter falls within the Average to Poor criteria.This evaluation serves as valuable input for stakeholders to improve and provide better public transportation services. ABSTRAK Peningkatan mobilitas masyarakat tidak lepas dari ketersediaan angkutan publik yang memadai, salah satunya adalah angkutan kota. Angkutan kota merupakan moda yang paling efektif untuk transportasi perkotaan. Untuk itu harus diikuti dengan peningkatan kualitas layanan armada angkutan kota tersebut. Penelitian ini bertujuan untuk mengukur kinerja operasional trayek angkutan umum di Kota Kendari. Metode penelitian yang digunakan adalah survei dinamis (dalam kendaraan) dan survei statis (ruas jalan). Parameter – parameter yang digunakan untuk menganalisis kinerja operasi dan mengukur kebutuhan trayek ini adalah frekuensi, faktor muat, time headway, waktu perjalanan, jumlah penumpang, ketersediaan, dan waktu sirkulasi. Pembobotan dilakukan melalui 5 kriteria yaitu Sangat Baik (5), Baik (4), Cukup (3), Buruk (2) dan Sangat Buruk (1). Hasil dari penelitian memperlihatkan bahwa angkutan kota dengan trayek R.01/R.02 pada kategori Baik, dan 6 trayek lainnya pada kategori Cukup. Adapun parameter Frekuensi, Time Headway dan Jumlah Kendaraan Operasional pada seluruh trayek berada pada kriteria Sangat Baik. Sedangkan parameter Faktor Muat pada kriteria Cukup hingga Buruk. Evaluasi ini dapat menjadi masukan bagi para pemangku kepentingan dalam menyediakan angkutan publik yang lebih baik.